Nilai Manfaat Total Gerhan di Sub DAS Tirto Jawa Tengah - Eka Widiyastutik; Bramasto Nugroho; Hariadi Kartodihardjo (Jurnal Manajemen Hutan Tropika, 2010)
One effort in improving productivity and regaining the function of forest and land which have been degraded is national movement on forest and land rehabilitation (Gerhan). This movement constitutes an investment. In general, an investment should always involve the expectation for obtaining benefit/profit, either directly or indirectly. The objective of this research was to estimate the magnitude of total benefits value resulting from Gerhan in Sub Watershed of Tirto located in Central Java Province. Benefits value was calculated by using market price approach, replacement cost, procurement cost, and contingency valuation methods. Economic value which was calculated consisted of direct use value, indirect use value, and non use value (option value and existence value). From rehabilitated land, as large as 1,463 ha (planting year 2003–2008) in the Tirto sub watershed, the present worth total economic value resulted from was Rp331,223,929,621 with analysis period of 15 years (cutting cycle of woody crop) at interest rate of 15% or Rp15,093,367 ha-1 year-1. Such value consisted of direct use value 92.21%, indirect use value of 6.64%, and non use value of 1.15%. These benefit value was calculated on the basis of planting success rate, namely 88% for woody crops and 85% for multi purpose tree species.